Are we born and do we die? - Lash, Nicholas (New blackfriars, 2009)
The stranglehold on our imagination by the mind-body dualisms that permeate the culture is such that most people seem to suppose that “body” and “soul” name distinct and separable entities. Resisting such dualisms in favour of an old-fashioned Aristotelean view of the soul as the form of the body, this essay considers two questions: do human parents produce human beings, and do human beings die? The doctrine of the special creation of the individual soul seems to require us to answer the first question in the negative because, according to this doctrine, parents only produce matter for the God-given soul to form. As to the second, many people seem to suppose that human beings do not die, only their bodies do. Arguing against the view that immortality is a natural property of human minds, the essay suggests (with the help of Joseph Ratzinger) that, whether we speak of “immortality” or of “resurrection”, life from death is neither nature, nor achievement, but gift.